The effects of pornography on sexual minority men's body image: an experimental study. Issue 4 (2nd October 2019) - Gleason, Neil; Sprankle, Eric
ABSTRACT: Pornography's effects on sexual minority men have not been extensively researched. Studies specifically examining its effects on body image in both heterosexual and sexual minority men have reported conflicting findings and have only used correlational and qualitative methods. This is this first known experimental study to investigate the impact of pornography on sexual minority men's body image. Eighty-seven sexual minority men were recruited for an online study. Participants were randomly assigned to watch either a pornographic video or nature video, and then completed three questionnaires assessing male genital self-image, drive for muscularity, and social physique anxiety. Results indicated that participants exposed to pornography did not report greater social physique anxiety, greater drive for muscularity, or reduced genital body image compared to participants exposed to the nature video. Self-reported history of pornography use was not associated with scores on the body image measures utilized. These results contradict previous findings indicating a positive correlation between pornography use and body dissatisfaction in sexual minority men, and further research is needed to explore these discrepancies.